MUTU ORGANOLEPTIK PEMPEK BERBAGAI JENIS IKAN ENDEMIK DAN TAKARAN TEPUNG TAPIOKA - Dasir Dasir; Alhanannasir Alhanannasir; Toni Wiropan (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2023)
Generally, endemic fish are only processed into salted fish. Pempek innovation by utilizing endemic fish is also necessary for local food diversification. This study aims to determine consumer acceptance based on the organoleptic quality of pempek with various types of endemic fish and tapioca flour dosage. The study used a Factorial Randomized Block Design (RAK Factorial) consisting of 2 treatments, namely the type of endemic fish (betok fish; Siamese gourami and lampam fish) and the dosage of tapioca flour from fish meat (0.5; 1; 2), each with three replications. Furthermore, the samples were tested using the hedonic test method including aroma, taste, color and ranking test for the elasticity parameter. The results showed that the best treatment was obtained in treatment J3T2 (lampam fish type with tapioca flour dosage 1) with scores for each parameter, namely aroma score 4.20 (preferred criteria), taste score 3.75 (slightly preferred criteria), color score 4.25 (preferred criteria) and chewiness score 4.35 (chewy criteria).